How can we achieve more sustainable water allocation in water-deficient areas? A case study from China’s Fen River Basin - Li, Chenchen; Wu, Jianwei (Frontiers in Environmental Science, 2023)
Achieving the goal of water resource allocation improvement is significant for the ecological conservation of basins. Considering the water supply and demand contradiction and the competition among stakeholders within water-deficient regions, we developed a multi-objective optimization model and proposed the most effective method for allocating water resources based on the study of supply and demand. This study reveals the following findings: 1) the total demand for the Fen River Basin in 2030 will be 6.68 billion m3. Compared with previous years, the actual consumption has increased, but the growth rate has slowed down. 2) The basin’s total supply of water in 2030 will be 7.855 billion m3. With the tightening of the management practice, the consumption and supply in each county showed a decreasing trend year by year. 3) The results of optimal water allocation for 2030 indicate that the FRB should allocate 1.655 billion m3 for domestic water, 4.57 billion m3 for production consumption, and 57 million m3 for ecological use.